2009
DOI: 10.1526/003601109789037222
|View full text |Cite
|
Sign up to set email alerts
|

Are Conventional Farmers Conventional? Analysis of the Environmental Orientations of Conventional New Zealand Farmers*

Abstract: Within the political economy of agriculture and agrofood literatures there are examples of approaches that reject simple dichotomies between alternatives and the mainstream. In line with such approaches, we challenge the assumption that alternative agriculture, and its attendant improved environmental practices, alternative management styles, less intensive approaches, and better approaches to animal and ecosystem welfare, is the only source of agricultural sustainability. This article uses national farm-surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Although issues related to soil, air and land use featured in the respondents' comments, there was more focus on both the views of the public on farming practices and government regulation (mostly referring to the fear of -more red tape‖). It is important however, to note that there is likely to be a significant group of farmers who are pursuing environmental issues due to their personal ethical values, rather than public and government pressure [18].…”
Section: Primary Producers-farmers and Their Organizationsmentioning
confidence: 99%
“…Although issues related to soil, air and land use featured in the respondents' comments, there was more focus on both the views of the public on farming practices and government regulation (mostly referring to the fear of -more red tape‖). It is important however, to note that there is likely to be a significant group of farmers who are pursuing environmental issues due to their personal ethical values, rather than public and government pressure [18].…”
Section: Primary Producers-farmers and Their Organizationsmentioning
confidence: 99%
“…This focus on broad-leaved herbaceous weed abundance and cover in pastures forms part of wider studies undertaken by the Agriculture Research Group on Sustainability (ARGOS 2010) that investigates the environmental, social and economic outcomes of different market accreditation systems as complementary pathways to more sustainable and resilient agriculture (Rosin & Campbell 2008, Fairweather et al 2009, Darnhofer et al 2010). This study of herbaceous weeds is part of a wider investigation of weed management options and techniques, pathways for invasion of woody weeds into agricultural land and assessment of future weed management research needs.…”
Section: Introductionmentioning
confidence: 99%
“…An important subgroup of 'green conventional' farmers identified in national survey responses (Fairweather et al 2009c) were represented in the ARGOS qualitative data by farmers and orchardists expressing such an orientation by prioritising a specific set of environmental outcomes: bird biodiversity as an indicator of orchard health or the overall amenity value of trees and other features like wetlands as hunting resources in their farmscapes . The members of the non-organic panels were also more likely to refer to a need to balance environmental concerns with economic viability and practicality.…”
Section: Positioning Towards Nature/environmentmentioning
confidence: 99%
“…Put simply, how do 'organic', 'conventional' and 'integrated' operate as social practices once we cease to conceptualise them as simple, categorical, and somehow determinative? Fairweather et al (2009c) identified a group of 'green' conventional farmers in New Zealand thus undermining a comfortable use of the category 'conventional' to describe the environmental practice of many producers. Similarly, Campbell et al (2009) in reviewing preliminary data from across the ARGOS project argued for the need to move beyond the organic/conventional binary.…”
Section: Beyond Categories Of Organic and Conventional Social Practicmentioning
confidence: 99%